2015
DOI: 10.1007/s00106-015-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Obliteration von Mastoidhöhlen

Abstract: In our experience, a combination of BAG S53P4 and cartilage as cover is a suitable material for cavity obliteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies reported on SSI after mastoid obliteration with BAG S53P4 in the management of chronic otitis media with and without cholesteatoma ( Bernardeschi, 2015 ; de Veij Mestdagh, 2017 ; Król, 2021 ; Leonard, 2021 ; Mishra, 2021 ; Sarin, 2012 ; Schimanski, 2015 ; Silvola, 2012 ; Sorour, 2018 ; Stoor, 2010 ; Vos, 2017 ) (see supplementary information, Table S2 ). The SSI rates in these studies vary from 0 to 2% and are lower compared to our rate of 12%, except for Silvola et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported on SSI after mastoid obliteration with BAG S53P4 in the management of chronic otitis media with and without cholesteatoma ( Bernardeschi, 2015 ; de Veij Mestdagh, 2017 ; Król, 2021 ; Leonard, 2021 ; Mishra, 2021 ; Sarin, 2012 ; Schimanski, 2015 ; Silvola, 2012 ; Sorour, 2018 ; Stoor, 2010 ; Vos, 2017 ) (see supplementary information, Table S2 ). The SSI rates in these studies vary from 0 to 2% and are lower compared to our rate of 12%, except for Silvola et al.…”
Section: Discussionmentioning
confidence: 99%
“…Schimanski et al. concluded that in the case of obliteration with BAG S53P4 postoperative use of a drain was beneficial to avoid accumulation of seroma fluid in the mastoid and thereby reducing the risk on an SSI ( Schimanski, 2015 ). Also, in other studies where a drain was used postoperatively no SSIs were reported ( Veij Mestdagh, 2017 ; Vos, 2017 ).…”
Section: Discussionmentioning
confidence: 99%